The broad effects of the functional IL-10 promoter-592 polymorphism: modulation of IL-10, TIMP-3, and OPG expression and their association with periodontal disease outcome - Marcela Claudino; Ana Paula F. Trombone; Cristina R. Cardoso; Samuel B. Ferreira, Jr; Walter Martins, Jr; Gerson F. Assis; Carlos F. Santos; Paula C. Trevilatto; Ana Paula Campanelli; João S. Silva; Gustavo P. Garlet (Journal of leukocyte biology, 2008)
Periodontal diseases are infectious diseases, in which periodontopathogens trigger chronic inflammatory and immune responses that lead to tissue destruction. It occurs through the generation of metalloproteinases and the activation of bone resorption mechanisms. Anti‐inflammatory cytokines such as IL‐10 seem to attenuate periodontal tissue destruction through the induction of tissue inhibitors of metalloproteinases (TIMPs) and the inhibitor of osteoclastogenesis osteoprotegerin (OPG). A high individual variation in levels of IL‐10 mRNA is verified in periodontitis patients, which is possibly determined by genetic polymorphisms. In this study, the IL‐10 promoter ‐592C/A single nucleotide polymorphism (SNP), which is associated with a decrease in IL‐10 production, was analyzed by RFLP in 116 chronic periodontitis (CP) patients and 173 control (C) subjects, and the IL‐10, TIMPs, and OPG mRNA expression levels in diseased gingival tissues were determined by real‐time‐PCR. The IL‐10‐592 SNP CA (P=0.0012/OR=2.4/CI:1.4‐4.1), AA (P=0.0458/OR=2.3/CI:1.1‐4.9), and CA+AA (P=0.0006/OR=2.4/CI:1.4‐3.4) genotypes and the allele A (P=0.0036/OR=1.7/CI:1.2‐2.4) were found to be significantly more prevalent in the CP group when compared with control subjects. Both CA and AA genotypes were associated with lower levels of IL‐10, TIMP‐3, and OPG mRNA expression in diseased periodontal tissues and were also associated with disease severity as mean pocket depth. Taken together, the results presented here demonstrate that IL10‐592 SNP is functional in CP, being associated with lower levels of IL‐10 mRNA expression, which is supposed to consequently decrease the expression of the downstream genes TIMP‐3 and OPG, and influence periodontal disease outcome.